BIOMARKERS, NEOANGIOGENESIS AND GROWTH FACTORS IN PANCREATIC CANCER - E. M. Frantsiyants; O. I. Kit; V. I. Aleynov; I. A. Goroshinskaya (Исследования и практика в медицине, 2019)
Pancreatic cancer (PC) is a lethal malignant tumor characterized by a rapid progression, invasiveness and resistance to radiochemotherapy. The development of biomarkers for the early diagnosis of the disease is relevant. Angiogenesis has been identified as a key factor in a number of pathological conditions, including cancer. The proangiogenic signaling molecule – vascular endothelial growth factor (VEGF) and its receptors play a central role in tumor angiogenesis. In this review, we also highlight the dual role of growth factor-β (TGF-β) and touch upon the prospects for therapeutic effects on targets associated with TGF-β signaling in pancreatic cancer. A growing interest is attracted to the role of insulin-like growth factors IGF-I and IGF-II in cancer diseases. IGF-I and its receptor are highly expressed on the surface of pancreatic cancer cell lines that initiate the transduction of intracellular signals associated with the proliferation, invasion and expression of angiogenesis mediators. And so, the study of markers and growth factors may be a new, viable option for the diagnosis and treatment of pancreatic cancer.